O controle penal no crime de lavagem de capitais - Bertoni, Felipe Faoro (2013)
The present research has as its aim the analysis of how is structured the system of criminal control of money laundering, its ways of performance as well as the main issued measures. Thus, it was verified the existence of a tendency both in the national and the international fields to intensify the preventive and repressive measures related to the delict of money laundering. Therefore, considering this finding, it was seeked the accomplish of an inspection on the publicized judgements by the research system of the Federal Regional Court of the 4th Region which were related, even indirectly, about money laundering in order to verify the congruence or not of the jurisprudence expression with the normative punitive intensification detected. The examination which took place on the mentioned decisions that formed the database of research allowed to achieve the conclusion that it is still expressionless the incidence of criminal law in the ambit of the complexity of the conducts occasionally outlined as delict of money laundering. In this way, it remains the indagation concerning to the correctness of the use of criminal law in dealing with these issues as effective actions and not merely symbolic.